ANALISIS CALENDAR ANOMALIES DI PASAR SAHAM INDONESIA TAHUN 1998 – 2018 - Hasna Fairuz Surachmadi; Anhar Fauzan Priyono; Heriyaldi Heriyaldi (EKUITAS (Jurnal Ekonomi dan Keuangan), 2021)
ABSTRACT   The Efficient Market Hypothesis Theory of Fama states that stock prices cannot be predicted by its movement tendency (random walk). In some stock markets, the movement of stock prices has a seasonal effect, which is the repetition of stock movements at a certain time that can be called a calendar anomalies. The repetition or seasonal effect on rate of return shows that the stock price can be predicted, thus it can be exploited by investors to get the probability of a higher rate of return. This research aims to see whether calendar anomalies prevail in the Indonesian stock market by using the daily and monthly rate of return of LQ45 and the Jakarta Composite Index (JCI) with an observation period of 21 years from 1998 to 2018 and estimated using the GARCH-M model (1,1). The results of this research are the existence of daily anomalies on Monday as the day with the lowest rate of return and Wednesday as the day with the highest rate of return. In addition, we also get the results of monthly anomalies in August as the month with the lowest rate of return and December as the month with the highest rate of return.